Developing the bounded inventory level policy as an inventory control mechanism for reentrant lines - Daway, Rhey David S. (2010)
Manufacturing systems involving reentrant lines have become quite common especially in the semiconductor industry. A reentrant line can be thought of as a queuing network wherein work-in-process (WIP) materials (such as water lots for example) visit one or more workstations, or service facilities, several times before eventually leaving the system. Now with the different buffers waiting to be processed at certain service facilities, and considering the fact that most of the workstations have limited or finite capacities, the complexity of the reentrant-line problem lies in the difficulty of determining the scheduling mechanism which results in the optimization of the performance of the system.